MULTI-CLASSIFICATION APPROACH FOR DETECTING THYROID ATTACKS - D.KERANA HANIREX; DR.K.P.KALIYAMURTHIE (International Journal of Pharma and Bio Sciences, 2013)
Thyroid is one of the crucial disease that affects people of all ages now a days. Diseases of the thyroid include conditions associated with excessive release of thyroid hormones (HyperThyroidism) and those associated with thyroid hormone deficiency ( Hypothyroidism) . In this paper we consider the Thyroid data set with multi class and propose the classification for thyroidism in a separate layer. In this work, a multi-classification approach for detecting thyroid attacks is designed to achieve higher efficiency and to improve the detection and classification accuracy.This method finds that the method NNge provides higher efficiency to classify the thyroid attacks